Publication Performance in German Academic Heart Surgery - Debus, Eike Sebastian; Dolg, Maximilian; Reichenspurner, Hermann; Grundmann, Reinhart T. (The Thoracic and Cardiovascular Surgeon, 2020)
Background This study was designed to evaluate the publication performance of management teams consisting of chief and senior physicians in German university cardiac surgery units over a 10-year period and to facilitate benchmarking.Methods The cutoff date for consideration of staffing from the unit Web site and publications was July 1, 2017. The literature search was based on an evaluation of the PubMed database. The 5-year impact factor (IF) from 2016 was assigned to each journal.Results Two thousand five hundred thirty-five publications (average IF 3.02) were registered, published in 323 journals. Of a total of 341 management team members, 235 (68.9%) published as first or last author over the 10-year period. The number of publications from the units divided into quintiles varied considerably with the first six units contributing 39.0% of all publications and the last nine units 9.4%. With a cumulative IF total of 3265, the publications of the first six units accounted for 42.7% of the cumulative IF, the last unit quintile amounted to 621 (8.1%) of the cumulative IF. When considering publications per managing member, the first quintile averaged 11.9 publications (29.6 IF) per managing member, the last quintile 3.3 publications (8.0 IF) per member.Conclusions The six units of the first quintile published on average 3.6 times more per managing member than the nine units in the last quintile and the average cumulative IF per member in the first quintile was almost five times higher. Further investigation must show whether this considerable difference in publication activity between the university units is also observed in other operative fields.
Keywords: cardiac surgery; university units; publication activity; impact factor; benchmarking